Upper pouch oesophageal duplication cyst- A rare association with Tracheoesophageal fistula: A case report - Deepa P. Makhija; Manish P. Khobragade; Abhijit Kumar; Rujuta S. Shah; Kedar P. Mudkhedkar; Rahul K. Gupta; Beejal V. Sanghvi; Sandesh V. Parelkar (EL-Med-Pub, 2021)
Background: Oesophageal atresia (OA) has associated anomalies in 50 to 70 % of cases. The usual associations include cardiac, gastrointestinal, anorectal, renal, vertebral, or skeletal anomalies. Oesophageal duplication cyst as an association in OA is extremely rare. Despite the related embryogenesis of these two anomalies, there are very few cases reported. Case Presentation: We present a low-birth-weight neonate with Type C Tracheo-oesophageal fistula (TEF) with an associated oesophageal duplication cyst. Conclusion: Upper pouch oesophageal duplication with TEF is very rare and this is the fourth case managed concomitantly at primary surgery in English literature available.